(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
This work is devoted to the study if issues related to the prevention of varicose veins, which is often among the population, through the analysis of the disease itself and its complications, simulation detection of the disease in the initial stages and assessment of the quality of life in such parents. Information is provided on the dynamics of its distribution in the world.